A Review of public private partnerships around girls' education in developing countries: flicking gender equality on and off. Issue 2 (June 2017) - Unterhalter, Elaine
Abstract: The article reviews the literature on Public Private Partnerships (PPPs) and policy on girls' schooling in developing countries. It considers the ways in which aims around gender equality and women's rights are positioned in policy texts concerned with girls' education PPPs. The argument made is that these documents exemplify an oscillation, using a multipolar register, between pragmatic initiatives that recognise existing sites of power, and attempts to develop a political project that dissolves differences between public and private constituencies, who share an interest in getting girls into school. The potential and limits of this approach to support integrated policy around rights and equalities is considered using the case of DFID's Girls' Education Challenge . An analytical framework is sketched that maps a political and epistemological process termed dispersal, which is used to consider some ways to investigate the effects of PPPs as a mechanism to address intersecting inequalities.